If it's not what You are looking for type in the equation solver your own equation and let us solve it.
X*X+(X+1)(X+1)=85
We move all terms to the left:
X*X+(X+1)(X+1)-(85)=0
Wy multiply elements
X^2+(X+1)(X+1)-85=0
We multiply parentheses ..
X^2+(+X^2+X+X+1)-85=0
We get rid of parentheses
X^2+X^2+X+X+1-85=0
We add all the numbers together, and all the variables
2X^2+2X-84=0
a = 2; b = 2; c = -84;
Δ = b2-4ac
Δ = 22-4·2·(-84)
Δ = 676
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$X_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$X_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$\sqrt{\Delta}=\sqrt{676}=26$$X_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(2)-26}{2*2}=\frac{-28}{4} =-7 $$X_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(2)+26}{2*2}=\frac{24}{4} =6 $
| 512+8y=121.5 | | (x^2-3x)^2-22(x^2-3x)+72=0 | | -29=6x+7(x-6) | | 26x+30=540 | | 0.5x-0.9+0.6=3.5 | | 5(20x+25)=1125 | | 3/8x-1/3+6=1/6x | | 2n+2=n-8 | | 540=26x+30 | | 5(83.4)+x/6=85 | | Y=x2+1 | | 540=36x+25 | | y=(1.86)1.49^8 | | y=(1.68)1.49^8 | | 18=5j+2+-9j | | -15=b=-8 | | 98=7(q−82) | | 49÷k–3=46 | | (1/v-4)-(4/v+2)=-3/v^2-2v-8 | | 16=10+3z | | 7b-7=3b+9 | | 3/8d-1/3=1/2 | | 5×+3y=56 | | 3w+9=18 | | 8^(x+1)=19 | | y=(35.97)0.63^3 | | y=(3.97)0.63^3 | | 10=3f=1 | | 2x=17=25 | | 2(y+7)-7y=19 | | 69=18k+36 | | 2/7x=17 |